The Gsp-1 genes encode the wheat arabinogalactan peptide. (March 2017) - Wilkinson, Mark D.; Tosi, Paola; Lovegrove, Alison; Corol, Delia I.; Ward, Jane L.; Palmer, Richard; Powers, Stephen; Passmore, Diana; Webster, Gina; Marcus, Susan E.; Knox, J. Paul; Shewry, Peter R.
Abstract: Western blotting, ELISA and 1 H-NMR spectroscopy showed that RNAi down-regulation of the wheat Gsp-1 gene resulted in reduced contents of both arabinogalactan peptide (AGP) and grain softness protein ( GSP-1 ) in mature wheat grains confirming that these components are encoded by the same gene. A small increase in grain hardness and decrease in the viscosity of aqueous extracts of the transgenic lines also indicated small effects on functional properties. Immunolocalisation using a novel wheat AGP monoclonal antibody in conjunction with confocal microscopy showed that the major form of AGP which was eliminated in knockout lines is located within the cell, probably in the vacuole, and not in the plasma membrane or cell wall. However, clear localisation of the AGP epitope to the plasma membrane was observed in both control and transgenic lines and probably resulted from the presence of one or more separate forms of arabinogalactan protein. The existence of such additional form(s) was also indicated by 1 H-NMR spectroscopy which showed that the ratio of arabinose to galactose differed between the control and transgenic lines. Highlights: RNAi-mediated suppression of Gsp-1 genes shows decreases in AGP and GSP content. First time demonstration that these two components are encoded by the same genes. Immunolabelling shows AGP has intracellular location, probably within vacuoles. Analysis of grain shows small but statistically significant effects on texture. Small but significant effects on viscosity of endosperm flour aqueous extracts.